2012
DOI: 10.1007/s12026-012-8269-7
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells and the malaria pre-erythrocytic stage

Abstract: Malaria remains one of the main infectious diseases in intertropical regions. The malaria parasite has a complex life cycle in its mammalian host, switching between variable forms as it traverses through different tissues and anatomic locations, either intra- or intercellularly. During its journey, the parasite encounters and interacts with the host immune system, which functions to prevent infections and limit ensuing pathologies. One important component of the host immune system is the dendritic cells (DC) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 109 publications
0
11
0
3
Order By: Relevance
“…During the Plasmodium infection, the parasite develops tropism towards DCs, which phagocytose the infected RBCs. 35,36 Inside DCs, the parasite produces hemozoin, a product of haemoglobin degradation, ultimately leading to impaired DC maturation. 12 In vitro hemozoin-treated DCs acquire immunosuppressive abilities such as reduced expression of co-stimulatory molecules CD80 and CD86, secretion of IL-10 and induction of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…During the Plasmodium infection, the parasite develops tropism towards DCs, which phagocytose the infected RBCs. 35,36 Inside DCs, the parasite produces hemozoin, a product of haemoglobin degradation, ultimately leading to impaired DC maturation. 12 In vitro hemozoin-treated DCs acquire immunosuppressive abilities such as reduced expression of co-stimulatory molecules CD80 and CD86, secretion of IL-10 and induction of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to malaria, the relative contribution of liver resident versus recruited inflammatory DC is unknown to date ( Mauduit et al, 2012 ). Several studies have demonstrated a critical role of CD8α + DCs in the activation of effector CD8 T cells responding to an epitope of CSP.…”
Section: The Hepatic Cycle Of Plasmodium —Implicatmentioning
confidence: 99%
“…When washed sporozoites were co-inoculated with or without mosquito saliva intradermally, the presence of saliva induced IL-4 and IL-10. Parasitemia was higher and cerebral malaria developed more frequently (Depinay et al, 2006;Schneider et al, 2011;Mauduit et al, 2012). The saliva of Aedes aegyti also exhibits immunomodulatory properties by inducing lymphocyte but not DC apoptosis in a caspase 3-and 8-dependent pathway (Bizzarro et al, 2013).…”
Section: Vector Saliva a Critical Parameter For Effective Pathogen Tmentioning
confidence: 99%